Volatile organic compounds in pea plants: a comprehensive review - Avesani, Sara; Castiello, Umberto; Ravazzolo, Laura; Bonato, Bianca (Frontiers in Plant Science, 2025)
Legumes are crops of significant global importance for ensuring food security, promoting sustainable production, and enhancing cropping efficiency within diverse agroecosystems. The pulse pea (Pisum sativum L.) is highly valued for its protein and micronutrient content, ranking third in global cultivation after soybeans and beans, with production mainly present in temperate regions. Pea production can be afflicted by crop losses due to biotic and abiotic stress factors, leading to an increased demand for improved defense systems. To cope with environmental stresses, plants have evolved several defense mechanisms, including the production of volatile organic compounds (VOCs), which are key in plant-to-plant communication and environmental interactions. Despite the growing interest in the characterization of plant VOCs in legumes, there has been a paucity of research on the emissions and functional roles of VOCs produced by peas, either constitutively or in response to various factors such as insects, pathogens, drought, and heat. In this review, we focused on the emission patterns and potential biological functions of VOCs produced by peas in response to various stimuli. Moreover, we discuss mass spectrometry techniques currently used or with potential applications for the study of pea VOCs. The emission of specific VOCs in response to external stimuli suggests a precise involvement in pea defense mechanisms. What emerges from this essay is that further functional studies are needed to enhance and exploit the potential of VOCs for sustainable applications, such as insect repellency, pathogen inhibition, and signaling in pea plant defense.